The making of urban Europe, 1000-1994 - Hohenberg, Paul M. (Harvard University Press, 1995)
Europe became a land of cities during the last millennium. The story told in this book begins with North Sea and Mediterranean traders sailing away from Dorestad and Amalfi, and with warrior kings building castles to fortify their conquests. It tells of the dynamism of textile towns in Flanders and Ireland. While London and Hamburg flourished by reaching out to the world and once vibrant Spanish cities slid into somnlence, a Russian urban network slowly grew to rival that of the West. Later as the tide of industrialization swept over Europe, the most intense urban striving and then settled back into the merchant cities and baroque capitals of an earlier era. By tracing the large-scale precesses of social, economic, and political change within cities, as well as the evolving relationships between town and country and between city and city, the authors present an original synthsis of European urbanization within a global context. They divide their study into three time periods, making the early modern era much more than a mere transition from preindustrial to industrial economies. Through both general analyzes and incisive case studies, Hohenberg and Lees show how cities originated and what conditioned their early development and later growth. How did urban activity respond to demographic and techological changes? Did the social consequences of urban life begin degradation or inspire integration and cultural renewal? New analytical tools suggested by a systems view of urban relations yield a vivid dual picture of cities both as elements in a regional and national heirarchy of central places and also as junctions in a transnational network for the exchange of goods, information, and influence. A lucid text is supplemented by numerous maps, illustrations, figures, and tables, and by substantial bibliography. Both a general and a scholarly audience will find this book engrossing reading. Table of Contents: Introduction: Urdanization in Perspective PART I: The Preindustrial Age: eleventh to Fourteenth Centuries 1. Structure and Functions of Medieval Towns 2. Systems of Early Cities 3. The Demography of Preindustrial Cities PART II: The Industrial Age: Fourteenth to Eighteenth Centuries 4. Cities in the Early Modern European Economy 5. Beyond Baroque Urbanism PART III: The Industrial Age: Eighteenth to Twentieth Centuries 6. Industrial and the Cities 7. Urban Growth and Urban Systems 8. The Human Consequences of Industrial Urbanization 9. The Evolution and Control of Urban Space 10. Europe's Cities in the Twentieth Century Appendix A: A Cyclical Model of an Economy Appendix B: Size Distributions and the Ranks-Size Rule Notes Bibliography Index Reviews of this book: A readable and ambitious introduction to the long history of European urbanization.--Economic History ReviewReviews of this book: A trailblazing history of the transformation of Europe.--John Barkham ReviewsReviews of this book: A marvelously compendious account of a millennium of urban development, which accomplishes that most difficult of assignments, to design a work that will safely introduce the newcomer to the subject and at the same time stimulate professional colleagues to review positions.--Urban Studies.